Proteomic profiles of floral and leaf tissues of Michelia alba DC - Hassan, Hasliza (2012)
Michelia alba DC is a well known fragrant plant that is rich in high quality essential oils of economic importance especially for the perfumery industry. At biochemical level, the exact metabolic pathway that is responsible for the generation of the essential oils in M. alba and the regulatory mechanism is poorly understood. Therefore, profiling of proteomes from the organs that are involved in the formation of the oils is an approach to obtain the potential candidate proteins related to the oils production. This study was carried out as an attempt to identify differentially expressed proteins during the development of fragrant-producing organs by optimizing the methods of protein extraction and profiling the proteomes at different developmental stages. The objectives of this study were i) to optimize the protein extraction protocols for profiling of M. alba proteomes by two-dimensional gel electrophoresis (2-DGE), ii) to optimize the reproducibility of two-dimensional polyacrylamide gel electrophoresis (2-DGE) in flower and leaf tissues of M. alba, iii) to profile the proteomes of the leaf and flower of M. alba using 2-DGE at different developmental stages of the organs, iv) to find trends and correlation of the proteomic profile in term of regulation of unique proteins and v) to identify uniquely proteins expressed for fragrance production throughout developmental stages. Two-dimensional gel electrophoresis (2-DGE) is currently one of the methods that can offer a relatively good separation power for proteomics analysis. In this study, traditional 2-DGE was used to profile the proteomes of the leaf and flower organs of M. alba at different evelopmental stages. A prerequisite for a reproducible, high resolution of proteomic protein separation on the 2-DGE, is the availability of protein extraction protocol that is optimized for the plant especially for M. alba as a woody plant. Three different protein extraction methods were evaluated for their abilities to extract high amounts of soluble protein, to produce high resolution of protein separation of the crude extract on 1D and 2D gels, and to eliminate maximum amounts of non-protein contaminants from the extract. The protocol based on the use of Bis-Tris/acetone was the best protein extraction protocol for M. alba based on the criteria above and was significantly highest in total protein content in both flower and leaf tissues (p<0.05). Using this protein extraction protocol, the proteomes of different developmental stages of M. alba leaf and flower were successfully resolved on 2-DGE. The numbers of protein spots and their expression levels were monitored during the development of the organs. Generally the numbers of protein spots increased during the development of the organs. During the development of M. alba flower, the numbers of protein spots reached its peak when the flower was about to open, but then decreased once the flower bloomed. Profiling of the leaf and flower proteomes from different developmental stages generated 80 to 210 spots, of which some showed differentially-expressed patterns. Five protein spots from the flower proteome and eight from the leaf were successfully identified based on peptide mass fingerprinting method. These proteins are categorized into three major classes according to their functions: primary metabolism, developmental and fragrancerelated proteins. Five of these are fragrance-related proteins namely 1- aminocyclopropane-1-carboxylic acid synthase, S-adenosylmethionine decarboxylase, guaiadiene synthase, acyl carrier protein 3 and caffeate omethyltransferase. The findings of the study provide some fundamental information for a more comprehensive approach to analyze and then explain the mechanism involved in fragrance biosynthesis and its regulation in this plant.